2020
DOI: 10.1177/1758573220917653
|View full text |Cite
|
Sign up to set email alerts
|

Glenoid bone grafting in primary anatomic total shoulder arthroplasty: a systematic review

Abstract: Background Primary anatomic total shoulder arthroplasty can be challenging in patients with complex glenoid wear patterns and bone loss. Severe retroversion (>15°) or significant bone loss may require bone grafting. This review summarizes the rate of revision and long-term outcomes of anatomic total shoulder arthroplasty with bone graft. Methods A systematic search of MEDLINE, Embase, PubMed, and CENTRAL databases was conducted from the date of inception to 23 October 2018. Two reviewers independently scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Bone grafting has a relatively low rate of revision surgery and a higher rate of patient satisfaction with 82% graft union rate [5]. Majorly autografts are used for structural stability and are the current gold standard for bone repairing and treating bone defects [1].…”
Section: Introductionmentioning
confidence: 99%
“…Bone grafting has a relatively low rate of revision surgery and a higher rate of patient satisfaction with 82% graft union rate [5]. Majorly autografts are used for structural stability and are the current gold standard for bone repairing and treating bone defects [1].…”
Section: Introductionmentioning
confidence: 99%
“…Sabesan et al reported substantial clinical and radiographic mid-term improvement of aTSA with an all-polyethylene glenoid component and autologous bone graft obtained from the humeral head [56]. A systematic review showed comparable revision rates and improvement in pain compared to augmented glenoid components and rTSA [57]. However, the use of a bone graft is complicated by the need for stable fixation of the bone graft prior to implantation of an all-polyethylene glenoid or the use of a metal-backed glenoid, which has demonstrated high rates of early failure [58].…”
Section: Glenoidmentioning
confidence: 99%